A CRITIQUE OF THE THEOCRATIC MODEL OF THE SULTANATE OF DELHI - TEHMEENA NOREEN (Hamdard Islamicus, 2021)
A number of historians have applied the term ‘theocracy’ for the political structure of the Delhi Sultanate. For them the Delhi Sultans were the Pope and Caesar combined in one. The sultans implemented Islamic sharÊ‘ah for all communities. The ulama exercised the strongest influence in political matters and the caliphs were considered to be the supreme sovereigns. The persecution of Hindus, their forceful conversions, destruction of temples and imposition of jizyah were all part of sultanate’s religious policy. This paper aims to rectify that these arguments are mainly generalizations based on few exceptions. The sultans had no religious authority nor was the sharÊ‘ah ever implemented. The sultans had only nominal allegiance to the caliphs and the majority of ulama worked for the sultans for their own vested interests. The conversions were also not forced although there were few exemptions but even they were politically motivated and same was the case with the destruction of temples.